Analisis Strategi Bersaing Pada KSPPS Hanada Quwais Sembada Kebasen Menggunakan Competitive Profile Matrix (CPM) - Rahmawati, Safira Aulia; Nurazizah, Khofifah; Maula, Muhammad Ihza; Shafrani, Yoiz Shofwa (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2025)
This study examines the competitive strategy of KSPPS Hanada Quwais Sembada Kebasen amidst intense competition in the microfinance sector, particularly against BPR Bank Surya Yudha Patikraja and PNM Mekar Sampang, which have advantages in technology and service coverage. This theme is chosen due to the importance of understanding the competitive position of community-based Islamic cooperatives to remain viable in the local market. This research employs a case study method with a qualitative descriptive approach. Data collection is conducted through interviews, observations, and documentation, which are then analyzed using the Competitive Profile Matrix (CPM) tool to assess the strengths and weaknesses of KSPPS Hanada relative to its main competitors, based on key factors such as market reputation, service quality, territorial coverage, product innovation, and technology utilization. The research findings indicate that KSPPS Hanada Quwais Sembada has advantages in market reputation, personalized service quality, and closeness to its members, but still lacks in territorial coverage and digital technology adoption. In conclusion, KSPPS Hanada Quwais Sembada needs to enhance innovation and service digitalization to compete better in the increasingly dynamic microfinance sector..